Influence of Post-UV/Ozone Treatment of Ultrasonic-Sprayed Zirconium Oxide Dielectric Films for a Low-Temperature Oxide Thin Film Transistor - Oluwabi, Abayomi Titilope (Materials (Basel), 2019)
Solution-processed metal oxides require a great deal of thermal budget in order to achieve the desired film properties. Here, we show that the deposition temperature of sprayed zirconium oxide (ZrO(x)) thin film can be lowered by exposing the film surface to an ultraviolet (UV) ozone treatment at room temperature. Atomic force microscopy reveals a smooth and uniform film with the root mean square roughness reduced from ~ 0.63 nm (UVO-O) to ~ 0.28 nm (UVO-120) in the UV–ozone treated ZrO(x) films. X-ray photoelectron spectroscopy analysis indicates the formation of a Zr–O network on the surface film, and oxygen vacancy is reduced in the ZrO(x) lattice by increasing the UV–ozone treatment time. The leakage current density in Al/ZrOx/p-Si structure was reduced by three orders of magnitude by increasing the UV-ozone exposure time, while the capacitance was in the range 290–266 nF/cm(2), corresponding to a relative permittivity (k) in the range 5.8–6.6 at 1 kHz. An indium gallium zinc oxide (IGZO)-based thin film transistor, employing a UV-treated ZrO(x) gate dielectric deposited at 200 °C, exhibits negligible hysteresis, an I(on)/I(off) ratio of 10(4), a saturation mobility of 8.4 cm(2) V(−1)S(−1), a subthreshold slope of 0.21 V.dec(−1), and a V(on) of 0.02 V. These results demonstrate the potentiality of low-temperature sprayed amorphous ZrO(x) to be applied as a dielectric in flexible and low-power-consumption oxide electronics.